Economic and Nafkah in the Case of Divorce in Indonesia: The Perspective of Fiqh - Sa'adah, Mazro'atus; Abubakar, Fatum; Na'mah, Ulin (IAIN Manado, 2024)
The number of divorce cases filed by wives is increasing. One of the factors considered to be the cause is the Nafkah issue. Accordingly, the discourse on the problem of sustenance as a reason for divorce among classical fiqh scholars and reinterpreting the text to find a solution to the high rate of divorce due to economic and living reasons, without having to leave the classical Islamic scholar’s legal tradition, needs to be studied more deeply. This research aims to provide a solution to prevent divorce caused by family conflicts due to economic factors by reviewing the concept of alimony from the perspective of fiqh. This research is qualitative, using a normative approach to fiqh and interpretation. The results of this study indicated that there was a need for reinterpretation of the views of the majority of scholars regarding the wife’s right to ask for a divorce from the judge if the husband does not provide a living. If the opinion of the fiqh scholars continues to be applied, it will increase the number of divorce cases for economic and livelihood reasons. Moreover, this action received legitimacy from stakeholders through marriage laws and regulations. The interpretation of KH. Husayn Muhammad’s of Q.S. al-Nisa' (4): 34 needs to be used as a reference in updating the law regarding the obligation of a living so that it is hoped that there will be no more divorces carried out for economic and livelihood reasons.